Benefits of a plant-based diet and considerations for the athlete - Shaw, K. A.; Zello, G. A.; Rodgers, C. D.; Warkentin, T. D.; Baerwald, A. R.; Chilibeck, P. D. (European Journal of Applied Physiology, 2022)
Individuals may opt to follow a plant-based diet for a variety of reasons, such as religious practices, health benefits or concerns for animal or environmental welfare. Such diets offer a broad spectrum of health benefits including aiding in the prevention and management of chronic diseases. In addition to health benefits, a plant-based diet may provide performance-enhancing effects for various types of exercise due to high carbohydrate levels and the high concentration of antioxidants and phytochemicals found in a plant-based diet. However, some plant-based foods also contain anti-nutrional factors, such as phytate and tannins, which decrease the bioavailability of key nutrients, such as iron, zinc, and protein. Thus, plant-based diets must be carefully planned to ensure adequate intake and absorption of energy and all essential nutrients. The current narrative review summarizes the current state of the research concerning the implications of a plant-based diet for health and exercise performance. It also outlines strategies to enhance the bioavailability of nutrients, sources of hard-to-get nutrients, and sport supplements that could interest plant-based athletes.